Mi cuerpo = My body [Board book] - Rosa-Mendoza, Gladys; Butler, Chris (Wheaton, IL : Me+mi Pub., 2002)
Introduces children to body parts in English and Spanish with illustrations. On board pages.
Text in English and Spanish.
Keywords: Human body -- Juvenile literature; Human body; Board books; Cuerpo -- Literatura juvenil; Spanish language materials -- Bilingual -- Fiction